Legal Protection Of Consumers Due To Breach In The Buying Of Housing - Widiarty, Wiwik Sri (LEGAL BRIEF, 2023)
Housing sale-purchase transactions are complex activities and are prone to default. The purpose of this research is to analyze the legal protection of consumers who experience defaults in housing sales and purchase transactions. This research uses normative legal research methods. The data collection technique in this research is done through literature study. The data is collected through a search of legal literature, laws and regulations related to housing sales and consumer protection, as well as court decisions relevant to cases of default in housing sales. The data sources used include books, scientific journals, articles, legal documents, and court decisions. The data collected is analyzed qualitatively using the content analysis method. The results show that the legal protection of consumers due to default in the sale and purchase of housing is in the form of contract law and consumer protection law. Legal efforts that can be made by the consumer if the perpetrator or seller of housing does not fulfill its obligations are by filing a lawsuit for compensation, mediation and arbitration based on default.